INTERNALISASI NILAI-NILAI KEUTAMAAN ILMU MELALUI PENGAJIAN LAILATUL I’TIROF BERBASIS KITAB KLASIK - Dwi Suryantoro (BAITUL JUHDI, 2025)
Abstract This community service activity was carried out through religious lectures in the Lailatul I'tirof recitation event at the Adz Dzikraa Islamic Boarding School, Situbondo. The focus of this activity is the internalization of the values of the virtues of knowledge in Islam through the approach of classical books (turats), especially the books Ta'lim al-Muta'allim and Bidayah al-Hidayah. The main purpose of this activity is to build awareness of the importance of knowledge as the foundation of charity, character, and self-transformation. The formulation of the problem in this activity includes how the classical book-based religious lecture method can strengthen the scientific value of students and its impact on the learning culture in Islamic boarding schools. The method used is in the form of educational lectures with a contextual approach, accompanied by strengthening the postulates of the Qur'an, hadiths, and stories of salaf scholars. The results of the activity showed a positive response, marked by an increase in students' motivation to learn, the growth of advanced book study initiatives, and the formation of a collective awareness of the importance of knowledge as a prophetic heritage and a means of character formation. Thus, this activity is one of the models of educational service that plays a role in strengthening the scientific tradition and spirituality of the Islamic boarding school. Keywords: Islamic Boarding School, Yellow Book, Virtue of Science, Santri, Community Service. Abstrak Kegiatan pengabdian kepada masyarakat ini dilaksanakan melalui ceramah keagamaan dalam acara pengajian Lailatul I’tirof di Pondok Pesantren Adz Dzikraa, Situbondo. Fokus kegiatan ini adalah internalisasi nilai-nilai keutamaan ilmu dalam Islam melalui pendekatan kitab klasik (turats), khususnya kitab Ta‘lim al-Muta‘allim dan Bidayah al-Hidayah. Tujuan utama kegiatan ini ialah membangun kesadaran santri terhadap pentingnya ilmu sebagai pondasi amal, karakter, dan transformasi diri. Rumusan masalah dalam kegiatan ini mencakup bagaimana metode ceramah keagamaan berbasis kitab klasik dapat memperkuat nilai keilmuan santri serta dampaknya terhadap budaya belajar di pesantren. Metode yang digunakan berupa ceramah edukatif dengan pendekatan kontekstual, disertai penguatan dalil Al-Qur’an, hadis, dan kisah ulama salaf. Hasil kegiatan menunjukkan respons positif, ditandai dengan meningkatnya motivasi belajar santri, tumbuhnya inisiatif kajian kitab lanjutan, serta terbentuknya kesadaran kolektif akan pentingnya ilmu sebagai warisan kenabian dan sarana pembentukan karakter. Dengan demikian, kegiatan ini menjadi salah satu model pengabdian edukatif yang berperan dalam memperkuat tradisi ilmiah dan spiritualitas pesantren. Kata Kunci: Pesantren, Kitab Kuning, Keutamaan Ilmu, Santri, Pengabdian Masyarakat.